PENGARUH BIAYA KUALITAS TERHADAP PERTUMBUHAN PENJUALAN DAN PROFITABILITAS - Kusmana, Muhammad Iqbal; Dahlan, Muhammad; Hasyir, Dede Abdul (JIPSI Jurnal Ilmu Politik dan Komunikasi, 2018)
The study aims to analyze the effect of quality costs on sales growth and profitability in regionaldrinking water companies (PDAMs). This study uses a quantitative approach. The population inthis study is quality costs in 391 PDAMs throughout Indonesia with a sample of 325 PDAMs. Thedata used is annual data from the realization of quality costs, sales growth rates, and profitmargins for three years, namely from 2015 to 2017. The results of this study indicate that qualitycosts have a significant positive effect on PDAM sales growth, with the percentage of influenceequal to 66.7%, while the remaining 33.3% is influenced by other factors not observed in this studyand quality costs have a significant positive effect on PDAM profitability, with a percentage effectof 59.5%, while the remaining 40.5% is influenced by other factors not observed in this study.